NILAI KEADILAN DALAM POLIGAMI - Dodon Alfiander (Institut Agama Islam Negeri Batusangkar, 2023)
This study examines the value of justice in polygamy from various perspectives, namely the Qur'an, Sunnah, ushul fiqh/fiqh, and positive law. This research is a literature study with data sources in the form of polygamy provisions contained in the Al-Qur'an, Sunnah, ushul fiqh/fiqh, and positive law. In addition, data were also taken from literature related to polygamy. Using a normative approach, this research finds that fairness is an important condition for polygamy. The concept of justice in the Qur'an tends to be related to business that is humanly possible. If someone really wants to do justice with a sincere goal, then he will not be able to do it considering his limitations as a human being. In principle, the concept of fairness in sunnah and ushul fiqh/fiqh refers to the interpretation of the Koran, namely fairness in the areas of living, muamalah, association, and night shifts. Meanwhile, justice in positive law basically emphasizes the husband's ability to be fair to his wives and children, especially in terms of subsistence. This research shows that in both Islamic law and positive law, justice is an important condition that must be met by a husband in polygamy.